Analysis Of The Effectiveness Of Audio Visual Learning Media Based On Macromedia Flash Usage On School Program Of Increasing Student Learning Motivation - Henny Sanulita; Donny Hendriyanto; Nana Citrawati Lestari; Akhmad Ramli; Opan Arifudin (Journal on Education, 2024)
The purpose of this study is to investigate the potential impact of flash multimedia audiovisual learning materials on students' motivation to learn. Quantitative and semi-experimental methodologies are used in this kind of research. An experimental design with just a post-test control group is used in this study. The population is represented by all study participants. The technique for gathering samples is called purposeful sampling. For the purposes of this sampling procedure, we selected two classes: class A served as the experimental group and class B as the control group. There were about a hundred pupils in the sample. Questionnaires were employed in order to gather data. The data analysis for this study included descriptive analysis. Students in the experimental class scored higher on the average for learning motivation than those in the control class, according to the findings of the descriptive statistical analysis. The significance level of 0.05 is not as great as the significance coefficient value of 0.000, according to the results of the t test hypothesis test. The findings of the t-test indicated that the experimental class was more driven to read documents regarding enthalpy changes than the control class. The impact of macromedia flash-based audio-visual learning materials on students' motivation to learn is probably the cause of this discrepancy.